Investigation of palladium recovery through cementation from spent automotive industry plating solutions - Çöke, Neslinur (My University, 2023)
Bu çalışmada, atık kaplama çözeltilerinden paladyum sementasyonunda metalik çinko ve kalay tozlarının kullanımı ve performanslarının karşılaştırılması incelenmiştir. Sementatör –çinko ve kalay miktarı, reaksiyon sıcaklığı ve reaksiyon süresinin paladyum çökelmesi (yüzde) üzerindeki etkileri derinlemesine incelenmiştir. Ayrıca, her bir sementatör için paladyum sementasyon kinetiği araştırılmış ve aktivasyon enerjilerinin Zn ve Sn için sırasıyla 4.2 kJ/ mol ve 12.6 kJ/ mol olarak bulunması reaksiyonun difüzyon kontrollü olduğunu göstermektedir. Kalaydan paladyum geri kazanımı, 200 mg kalay tozu kullanıldığında bile %100'e ulaşmazken, 40 dakikada paladyumun tam sementasyonu için 30 mg çinko yeterliydi. Çinko miktarı 100 mg'a ulaştığında 10 dakikada semantasyon tamamlandı. Ancak paladyumun kalay ile sementasyonu, 1 saat sonunda 200 mg kalay ile %100 değil, sadece %80'in üzerine çıkmıştır.

The use of metallic zinc and tin powders to cement palladium from waste plating solutions and the comparison of their performance were examined in this study. The effects of cementator –zinc and tin-quantity, reaction temperature, and reaction time on palladium precipitation (percent) were studied in depth. Furthermore, the palladium cementation kinetics were investigated to every different cementator, and it was discovered that the activation energies are 4.2 kJ/ mol and 12.6 kJ/ mol for Zn and Sn, respectively, indicative of the fact that the reaction is regulated by diffusion. The palladium recovery from tin did not reach 100% even when using 200 mg of tin powder, while 30 mg zinc was enough for the complete cementation of palladium at 40 min. When the quantity of zinc reached to 100 mg, the cementation was completed after 10 min. However, the cementation of palladium by tin did not attain to 100 % but only to over 80 % using 200 mg tin at the end of 1 h.
Kullanılmış otomotiv sektörü kaplama çözeltilerinden sementasyon ile paladyum geri kazanımının araştırılması
Keywords: Atık kaplama solüsyonu; Cementation; Geri kazanım; Metallurgy and materials engineering; Metalurji ve malzeme mühendisliği; Pd; Recovery; Sementasyon; Waste plating solution